Age specific anatomical studies on the medulla oblongata in post hatch broiler chicken - Gautam, Avnish Kumar; Ray, Sanjay; Das, Partha; Mandal, Arun Kumar; Tudu, Nirmal Kumar; Sinha , Manoj Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Present work was conducted on the seventy (70) day old broiler chicks which were reared up to 42 days (market age) of post hatch period. The whole experimental period of study was divided into seven (07) groups, each containing ten (10) birds irrespective of sex accordingly. The medulla oblongata was situated behind the optic lobes just ventral to the cerebellum and it became gradually narrowed posterior. The medulla oblongata at all the age groups was made up of chiefly the broad bands of nerve fibres, which were longitudinally placed. The nuclei of the medulla oblongata were formed by few multipolar neurons, spindle shape neurons and very few pyramidal neurons supported by few neuroglia cells. A weak to mild lipofuscin pigmentation in neurons of medulla oblongata was observed in group I, while in group VII, moderate pigmentation was recorded.